Визначення прогнозних обсягів попиту на електроенергію у воєнний та повоєнний час в Україні на базі макроекономічних факторів розвитку її економіки - Maistrenko, Natalia (General Energy Institute of the National Academy of Sciences of Ukraine, 2026)
The article examines the influence of macroeconomic factors of the Ukrainian economy on the volume of demand in the types of economic activity (TEA) and the population. The main factor today and in the near future remains the forecast of Ukraine's gross domestic product (GDP). Among the world institutions that provided such a forecast are the International Monetary Fund (IMF), the World Bank, the European bank for reconstruction and Development (EBRD), and the National Bank of Ukraine. According to the author, the most likely forecast is the IMF, which consists of basic and negative scenarios for the further development of the Ukrainian economy. Based on these scenarios, a forecast of Ukraine's GDP in constant prices from 2021 to 2030 has been developed. The article takes into account the trends in the Ukrainian economy that developed in 2022‒2024, on the basis of which the forecast structure of the Ukrainian economy according to the baseline scenario in actual prices is proposed, which is the next factor for forming a forecast of electricity demand. Using a comprehensive method of forecasting energy demand, the calculation of possible volumes of electricity demand for the country as a whole, for sectors (enlarged sections) of the Ukrainian economy and for the population is carried out. According to the baseline scenario, electricity consumption is expected to resume to the level of 2020 in the main sections of the economy by 2030, by 2040 it is possible to restore demand for electricity in industrial sections of the economy on the basis of modernization of energy-intensive industries and the construction of new enterprises, including the military-industrial complex.